Synthesis and spectroscopic properties of β-meso directly linked porphyrin–corrole hybrid compounds - Temelli, Baris; Kalkan, Hilal (Beilstein Journal of Organic Chemistry, 2018)
The preparation of β-meso directly linked porphyrin–corrole hybrids was realized for the first time via an InCl3-catalyzed condensation reaction of 2-formyl-5,10,15,20-tetraphenylporphyrins with meso-substituted dipyrromethanes. Hybrid compounds have been characterized by 1H NMR, 13C NMR, 2D NMR, UV–vis absorption and fluorescence spectroscopy.
Keywords: corrole; hybrid compounds; indium(III) chloride; porphyrin; porphyrinoids

The Porphyrin Handbook - Kadish, K. M.; Smith, K. M.; Guilard, R. (Academic Press, 2000)

The Porphyrins - Dolphin, D. (Academic Press, 1979)

(untitled) - Beletskaya, I.; Tyurin, V. S.; Tsivadze, A. Y.; Guilard, R.; Stern, C. (Chem. Rev., 2009)

(untitled) - Wasielewski, M. R. (Chem. Rev., 1992)

(untitled) - Panda, D. K.; Goodson, F. S.; Ray, S.; Saha, S. (Chem. Commun., 2014)

(untitled) - Senge, M. O.; Fazekas, M.; Notaras, E. G. A.; Blau, W. J.; Zawadzka, M.; Locos, O. B.; Mhuircheartaigh, E. M. N. (Adv. Mater., 2007)

Handbook of Porphyrin Science, Synthetic Strategies Toward Multiporphyrinic Architectures - Aratani, N.; Osuka, A. (World Scientific, 2010)

(untitled) - Tanaka, T.; Osuka, A. (Chem. Soc. Rev., 2015)

Multiporphyrin Arrays: Fundamentals and Applications - Kim, D. (Pan Stanford, 2012)

(untitled) - Drovetskaya, T.; Reed, C. A.; Boyd, P. (Tetrahedron Lett., 1995)

(untitled) - Ciammaichella, A.; Dral, P. O.; Clark, T.; Tagliatesta, P.; Sekita, M.; Guldi, D. M. (Chem. – Eur. J., 2012)

(untitled) - Pelado, B.; Abou-Chahine, F.; Calbo, J.; Caballero, R.; de la Cruz, P.; Junquera-Hernández, J. M.; Orti, E.; Tkachenko, N. V.; Langa, F. (Chem. – Eur. J., 2015)

(untitled) - Lee, C. Y.; Hupp, J. T. (Langmuir, 2010)

(untitled) - Kursunlu, A. N. (RSC Adv., 2014)

(untitled) - Liu, J.-Y.; Ermilov, E. A.; Röder, B.; Ng, D. K. P. (J. Porphyrins Phthalocyanines, 2013)

(untitled) - Guilard, R.; Jérôme, F.; Gros, C. P.; Barbe, J.-M.; Ou, Z.; Shao, J.; Kadish, K. M. (C. R. Acad. Sci., Ser. IIc: Chim., 2001)

(untitled) - Guilard, R.; Burdet, F.; Barbe, J.-M.; Gros, C. P.; Espinosa, E.; Shao, J.; Ou, Z.; Zhan, R.; Kadish, K. M. (Inorg. Chem., 2005)

(untitled) - Kadish, K. M.; Shao, J.; Ou, Z.; Frémond, L.; Zhan, R.; Burdet, F.; Barbe, J.-M.; Gros, C. P.; Guilard, R. (Inorg. Chem., 2005)

(untitled) - Kadish, K. M.; Shao, J.; Ou, Z.; Zhan, R.; Burdet, F.; Barbe, J.-M.; Gros, C. P.; Guilard, R. (Inorg. Chem., 2005)

(untitled) - Kadish, K. M.; Frémond, L.; Ou, Z.; Shao, J.; Shi, C.; Anson, F. C.; Burdet, F.; Gros, C. P.; Barbe, J.-M.; Guilard, R. (J. Am. Chem. Soc., 2005)

(untitled) - Flamigni, L.; Ventura, B.; Tasior, M.; Gryko, D. T. (Inorg. Chim. Acta, 2007)

(untitled) - Nikolaou, V.; Karikis, K.; Farré, Y.; Charalambidis, G.; Odobel, F.; Coutsolelos, A. G. (Dalton Trans., 2015)

(untitled) - Ngo, T. H.; Zieba, D.; Webre, W. A.; Lim, G. N.; Karr, P. A.; Kord, S.; Jin, S.; Ariga, K.; Galli, M.; Goldup, S.; Hill, J. P.; D’Souza, F. (Chem. – Eur. J., 2016)

(untitled) - Soares, A. R. M.; Martinez-Diaz, V. M.; Bruckner, A.; Pereira, A. M. V. M.; Tomé, J. P. C.; Alonso, C. M. A.; Faustino, M. A. F.; Neves, M. G. P. M. S.; Tomé, A. C.; Silva, A. M. S.; Cavaleiro, J. A. S.; Torres, T.; et al. (Org. Lett., 2007)

(untitled) - Pereira, A. M. V. M.; Soares, A. R. M.; Hausmann, A.; Neves, M. G. P. M. S.; Tomé, A. C.; Silva, A. M. S.; Cavaleiro, J. A. S.; Guldi, D. M.; Torres, T. (Phys. Chem. Chem. Phys., 2011)

(untitled) - KC, C. B.; Lim, G. N.; D’Souza, F. (Nanoscale, 2015)

(untitled) - Inokuma, Y.; Hayashi, S.; Osuka, A. (Chem. Lett., 2009)

(untitled) - Tanaka, T.; Aratani, N.; Lim, J. M.; Kim, K. S.; Kim, D.; Osuka, A. (Chem. Sci., 2011)

(untitled) - Mori, H.; Tanaka, T.; Lee, S.; Lim, J. M.; Kim, D.; Osuka, A. (J. Am. Chem. Soc., 2015)

(untitled) - Honjo, K.; Mori, H.; Osuka, A. (Asian J. Org. Chem., 2016)

(untitled) - Orlowski, R.; Gryko, D.; Gryko, D. T. (Chem. Rev., 2017)

(untitled) - Barata, J. F. B.; Neves, M. G. P. M. S.; Faustino, M. A. F.; Tomé, A. C.; Cavaleiro, J. A. S. (Chem. Rev., 2017)

(untitled) - Aviv, I.; Gross, Z. (Chem. Commun., 2007)

(untitled) - Chen, C.; Zhu, Y.-Z.; Fan, Q.-J.; Song, H.-B.; Zheng, J.-Y. (Chem. Lett., 2013)

(untitled) - Murugavel, M.; Reddy, R. V. R.; Sankar, J. (RSC Adv., 2014)

(untitled) - Murugavel, M.; Reddy, R. V. R.; Dey, D.; Sankar, J. (Chem. – Eur. J., 2015)

(untitled) - Hiroto, S.; Hisaki, I.; Shinokubo, H.; Osuka, A. (Angew. Chem., Int. Ed., 2005)

(untitled) - Temelli, B.; Ozasik, O.; Yüksel, D. (Eur. J. Org. Chem., 2017)

(untitled) - Gryko, D. T. (J. Porphyrins Phthalocyanines, 2008)

(untitled) - Koszarna, B.; Gryko, D. T. (J. Org. Chem., 2006)

(untitled) - Götz, D. C. G.; Bruhn, T.; Senge, M. O.; Bringmann, G. (J. Org. Chem., 2009)

(untitled) - Littler, B. J.; Ciringh, Y.; Lindsey, J. S. (J. Org. Chem., 1999)